Are we overestimating recovery of sturgeon populations using mark/recapture surveys?. (19th September 2018) - Haxton, Tim J.; Friday, Mike J.
Abstract: Mark‐recaptures studies are often conducted to monitor trends in sturgeon populations. However, many of these studies experience low recapture rates, minimal movement between marking‐recapture phases suggesting that sturgeon as a group are not conducive to mark‐recapture techniques. In this study, two mark‐recapture studies that were conducted differently were reviewed. A study was conducted on the Mattagami River using random nets set throughout the study area in both the mark and recapture phases. The other study was conducted on Lake of the Woods and marked sturgeon in tributaries during the spawning period and the recapture phase within the lake and river during the summer foraging period using random nets sets. Sturgeon's conduciveness to mark‐recapture studies was assessed on the Mattagami River mark‐recapture study by determining detection probability ( p ) using a hierarchical Bayesian model with data augmentation among three effects: individual effect, temporal effects, and behavioural response effects. Detection probability was constant over individuals and temporally suggesting model M 0 (Otis, Burnham, White, & Anderson, 1978 ) was suitable for lake sturgeon in the Mattagami River; only the M 0 would converge for the Lake of the Woods study. For this study, the assumption that "all individuals have the same probability of being captured during the marking phase" was believed to have been violated given approximately 16%–20% of adult Lake Sturgeon from a population spawn within a year. A population estimate accounting for p provided estimates 56% lower than calculated by a Chapman modification of the Peterson estimate for a closed population. Bias was believed to have been introduced as the Lake of the Woods population did not account for the non‐spawning adults that were encountered during the recapture phase and not vulnerable during the initial marking phase. This was not unique to the Lake of the Woods study as other sturgeon studies, especially multi‐year, assumes a closed population which potentially biased estimates and overestimated their recovery.